Alternative splicing as a source of phenotypic diversity - Wright, Charlotte J; Smith, Christopher W. J; Jiggins, Chris D (Nature reviews. Genetics, 2022)
A major goal of evolutionary genetics is to understand the genetic processes that give rise to phenotypic diversity in multicellular organisms. Alternative splicing generates multiple transcripts from a single gene, enriching the diversity of proteins and phenotypic traits. It is well established that alternative splicing contributes to key innovations over long evolutionary timescales, such as brain development in bilaterians. However, recent developments in long-read sequencing and the generation of high-quality genome assemblies for diverse organisms has facilitated comparisons of splicing profiles between closely related species, providing insights into how alternative splicing evolves over shorter timescales. Although most splicing variants are probably non-functional, alternative splicing is nonetheless emerging as a dynamic, evolutionarily labile process that can facilitate adaptation and contribute to species divergence.In this Perspective, the authors discuss how regulated alternative splicing can generate phenotypic diversity and outline emerging evidence that alternative splicing contributes to adaptation and species divergence.